Surface-bound humic acid increased rhodamine B adsorption on nanosized hydroxyapatite. Issue 5 (4th May 2017) - Wang, Gang; Qi, Jingjing; Wang, Shuangyan; Wei, Zhenggui; Li, Shiyin; Cui, Jing; Wei, Wei
ABSTRACT: In this study, humic acid-bound nanosized hydroxyapatite (HA-nHAP) was developed as a novel adsorbent, and the potential of using HA-nHAP for the adsorption of rhodamine B (RhB) from aqueous solution as functions of pH, adsorbent dosage, contact time, ionic strength, and temperature was investigated. The results indicated that the HA binding significantly increased the adsorption of RhB due to the introduction of abundant negatively charged functional groups. The adsorption capacity of HA-nHAP for RhB was found to be pH-dependent, and the optimal pH value was found to be 6.0. The adsorption equilibrium data obeyed Sips and Freundlich isotherms and the kinetic data were well described by the Elovich kinetic model. According to the Sips equation, the maximum adsorption capacity for RhB was 24.12 mg/g. The temperature and ionic strength experiment showed that they both had an effect on the adsorption capacity of HA-nHAP. Thermodynamic study confirmed that the adsorption was a spontaneous, endothermic, and more random arrangement process. The present investigation showed that HA-nHAP is a promising adsorbent for the removal of RhB from aqueous solution. GRAPHICAL ABSTRACT: